Analisis Pengaruh Pelaksanaan Manajemen Sumber Daya Manusia Terhadap Kepatuhan Keselamatan dan Kesehatan Kerja - Pratika, Ayu; Prakoso, A Aulia Firli Putri; Yusran, Nur Fitrah; Azis, Ismi Nur Maharani; Ginting, Chris Dayanti Br (Annusfy : Journal of Multidisciplinary Research, 2025)
This study analyzes the effect of Human Resource Management (HRM) implementation on compliance with Occupational Health and Safety (OHS) practices across various industrial sectors. Through a systematic literature review of 15 national and international journal articles  the research focuses on HRM functions like training, supervision, and developing a safety-oriented work culture. The results show that effective HRM significantly enhances employee awareness, responsibility, and discipline in adhering to OHS procedures. The integration of HRM with OHS systems positively contributes to reducing workplace accidents, increasing productivity, and improving organizational performance. The findings confirm HRM’s strategic role as a key driver of sustainable OHS implementation, necessitating comprehensive integration of HR policies and OHS systems to embed a safety culture in employee behavior